Exploring the Users’ Satisfaction with Library Resources and ICT-Based Services: A Case Study of Magadh University, Bodh Gaya, Bihar, India (LIS TODAY, 2025)
This study investigates user satisfaction with library resources and Information and  Communication Technology (ICT) based services at Magadh University, Bodh Gaya, Bihar,  India. The research employs survey research method, combining structured questionnaire  to assess the effectiveness of library services and resources. A sample of 500 students and  faculty members participated in the study. Results indicate a moderate level of satisfaction  with traditional library resources but highlight significant gaps in ICT-based services. The  study recommends strategic improvements in digital resources, ICT infrastructure, and  user training to enhance overall user satisfaction and library effectiveness.
Keywords: Library resources; ICT services; User satisfaction; Academic Libraries; Magadh University